Do β-Defensins and Other Antimicrobial Peptides Play a Role in Neuroimmune Function and Neurodegeneration? - Williams, Wesley M. (The Scientific World Journal, 2012)
It is widely accepted that the brain responds to mechanical trauma and development of most neurodegenerative diseases with an inflammatory sequelae that was once thought exclusive to systemic immunity. Mostly cationic peptides, such as the β-defensins, originally assigned an antimicrobial function are now recognized as mediators of both innate and adaptive immunity. Herein supporting evidence is presented for the hypothesis that neuropathological changes associated with chronic disease conditions of the CNS involve abnormal expression and regulatory function of specific antimicrobial peptides. It is also proposed that these alterations exacerbate proinflammatory conditions within the brain that ultimately potentiate the neurodegenerative process.